Branding Kebun Raya Mangrove Surabaya Melalui Pembuatan Suvenir - Tutiasri, Ririn Puspita; Kusuma, Ade; Setiawan, Bayu; Sumardjijati, Sumardjijati; Fauzi, Reza Mehdi; Santoso, Wahyu (Indonesian Journal of Society Engagement, 2024)
Kebun Raya Mangrove Surabaya (KRM) is an ecotourism destination focused on mangrove ecosystem conservation and environmental education. To enhance its appeal, build a positive image, and strengthen local economic sustainability, the development of eco-friendly souvenirs rooted in local wisdom presents a promising branding strategy. Souvenirs such as bucket hats, hand fans, brooches, and keychains with mangrove-inspired designs serve not only as promotional tools but also as educational mediums for environmental awareness among tourists. This article presents the results of a community service project aimed at creating souvenir concepts that support KRM’s branding, involving local communities in the production process, and promoting sustainability principles in tourism. The methods employed include training in creative design, producing eco-friendly souvenirs, and implementing digital marketing strategies. The findings indicate that souvenir development can increase tourists' awareness of mangrove ecosystem conservation while positively impacting local communities through income generation and skill development. This souvenir-based branding strategy not only reinforces KRM’s identity as an educational ecotourism destination but also supports environmental preservation and sustainable economic development.